USE OF PRODUCTS IN EARLY CHILDREN'S MATHEMATICS LEARNING - Dyantari, Putu; Parisangga, Gusti Gede Diva (JARITA : Journal of Children’s Education and Learning Research, 2025)
This research is qualitative research using the literature study method. Literature study is a series of activities relating to methods of collecting library data, reading and taking notes, and managing materials. This research aims to determine efforts to use teaching aids in mathematics learning in early childhood. The results of this research show that the use of mathematics learning tools, especially mathematics teaching aids, can be categorized as a positive result, because using teaching aids can help and facilitate the introduction of mathematics learning and mathematical skills by teachers to children and have a positive impact in increasing children's attention in create interesting and fun learning activities. The use of props is also categorized as a fairly efficient result. Because the impact can be observed in real terms, namely by the high level of enthusiasm and enthusiasm for learning shown by children during teaching and learning activities. In general, the use of teaching aids in mathematics learning in early childhood has an impact on children's understanding and active learning in the classroom.